Adiposity during adolescence and carotid intima-media thickness in adulthood: Results from the 1993 Pelotas Birth Cohort. (December 2016) - Menezes, Ana Maria Baptista; da Silva, Cristiano Tschiedel Belem; Wehrmeister, Fernando César; Oliveira, Paula Duarte; Oliveira, Isabel O.; Gonçalves, Helen; Assunção, Maria Cecilia F.; de Castro Justo, Fabiano; Barros, Fernando C.
Abstract: Background and aims: Although several studies have examined the association between adiposity and cardiovascular risk markers, few have explored the issue prospectively in young populations. We sought to test whether higher levels of body mass index (BMI) and subscapular skinfold at different stages of adolescence were associated with carotid intima-media thickness (cIMT) in young adulthood. Methods: In a prospective cohort, we assessed BMI and subscapular skinfold at 11, 15 and 18 years and measured cIMT at 18 years in 3264 individuals. Traditional cardiovascular risk factors and fat mass-mediating effects on cIMT were also assessed. Results: Both BMI and subscapular skinfolds were significantly associated with higher cIMT in a cummulative fashion: after controlling for confounders, males and females who persisted overweight/obese at all three assessments, had a mean higher cIMT (5.2 and 3.1 μm, respectively) compared to males and females with normal/healthy BMI at each evaluation ( p  < 0.001). Moreover, male and females that presented increased fatness in all assessments had a similar pattern of higher cIMT compared to normal/healthy fatness/skinfold at 18 years (mean cIMT 4.6 and 3.0 μm for males and females, respectively; p  < 0.001). Associations between adiposity and cIMT were both direct and indirect. Indirect effects were chiefly mediated by fat mass and diastolic blood pressure. Conclusions: Our results suggest adiposity exerts direct and indirect effects during adolescence that result in higher cIMT in young adulthood. Highlights: High BMI and subscapular skinfolds during adolescence are associated with higher cIMT at 18 years. Adiposity exerts direct and indirect effects on cIMT. Indirect effects are chiefly mediated by fat mass and diastolic blood pressure.